Semiotic Approach in the Development of Interactive Visual Analytics Systems; CEUR Workshop Proceedings; Vol. 2744 : GraphiCon 2020. Computer Graphics and Machine Vision - Zakharova A. A. Alyona Aleksandrovna (2020, 2020)
Title screen